A situacao do feijao (Phaseolus vulgaris e Vigna) no Brasil com algumas sugestoes para a politica - Sanders, J.H.; Nicoleti, GH (International Center for Tropical Agriculture, 1979)
Bean production trends during the years of 1947-51 and 1973-77 were analyzed for the different states of Brazil and some marketing policies for surplus crops are suggested. The state of Parana was the largest producer during 1947-51 and 1973-77 with 203,506 and 561,360 t, resp., representing 20.7 and 31.5 percent of the total national production. Bean yields decreased during the period 1973- 77 with values ranging between 2.6 percent for Sao Paulo and 55.4 percent for Ceara. Bean production decreased with the introduction of other crops such as cotton and soybean, host plants of the whitefly (Bemisia tabaci), vector of BGMV, and therefore competing for area dedicated to bean production. Prices vary widely, especially for some var. due to consumer preferences. Suggestions include policies of bean storage to eliminate seasonal variation in price and protect both the consumer and the producer, development of disease-resistant var., and survey of consumer preferences of bean var. Tables and figures are included for analyzing the observed trends. (CIAT)